(untitled) (Ozone Therapy Global Journal, 2017)
The Spanish Journal of Ozone Therapy comes on time once more to its annual appointment. Aepromo is pleased to present its 7th issue, making available to its readers the scientific work of researchers in the field of ozone therapy. So Aepromo reaffirms its commitment to continue supporting ozone therapy from a platform of prestige and reference in the scientific world. So far, it is the only indexed journal specialized in ozone therapy that has been sustained for eight years, when we published the No. zero in 2010. In addition to the annual issue of each May we have published seven supplements.